Analysis of the ability to understand junior high school mathematics concepts in the material of quadrilaterals - Amanda Nur Lailiyatul Faizza; Agus Qowiyuddin; Khoirul Huda (Jurnal Riset Pendidikan Matematika Jakarta, 2024)
Build a flat quadrangle It is a certain line segment which is joined by four points where the points are not in a line, which in pairs meet at the ends and each line segment must meet with two corners which are formed called the corners in a quadrilateral with the corner points being the four points the. Quadrilateral shapes include squares, rectangles, parallelograms, rhombuses, kites and trapezoids. (Nadjib, 2014) The aim of this research is to determine and describe the ability to understand mathematical concepts of rectangular flat shapes at Al-Hidayah Sukorejo Middle School Class VII. The research is qualitative research with a descriptive approach. The data collection technique is a sampling technique. From 37 students we take 4 students from the highest score to the lowest score. The results will show their respective understanding abilities towards the mathematical concept of flat shapes.